Integrating Modern Pesantren Values into the KMI Curriculum at Gontor Putri: A Qualitative Field Study on Female Students’ Character Formation - Rosyidah, Umi; Ahmad Hasan Al Banna; Hasan Ruzakki; Hosaini (Mimbar Agama Budaya, 2025)
This article examines how the values of modern boarding schools are integrated into the curriculum of Kulliyyatu-l-Mu'allimāt al-Islāmiyah (KMI) at Pondok Modern Darussalam Gontor Putri, as well as how these strategies shape the character of students. Values such as sincerity, simplicity, independence, Islamic ukhuwah, and freedom serve as the foundation of education, integrated into the formal learning process and the life of a 24-hour Islamic boarding school. This study uses a descriptive, qualitative approach grounded in the literature and data validation through source triangulation. The results of the study show that the KMI curriculum is an integrated curriculum that combines religious and general lessons in proportion and is implemented through active learning strategies, direct instruction, strict supervision, and character development through teacher examples. Thus, the integration of modern boarding school values is not only part of the academic structure but also transforms into a character-education system that shapes students into tough, intelligent, and noble individuals.